Plasma homocysteine concentration is not associated with activated protein C resistance in patients investigated for hypercoagulability - Zarychanski, Ryan; Houston, Donald S. (Thrombosis and Haemostasis, 2004)
Homocysteine and activated protein C (aPC) resistance are known risk factors for thromboembolism, but how elevated homocysteine influences thrombogenicity is not fully understood. The possibility that homocysteine may exert a prothrombotic effect by inducing aPC resistance has been addressed, with conflicting conclusions. The aim of this study is to evaluate the possible relationship of serum homocysteine concentration to aPC resistance in a cohort of patients investigated for hypercoagulability. Laboratory records from 1011 consecutive patients referred to the Haemostasis Laboratory at the Health Sciences Centre (Winnipeg, Canada) were reviewed from February 1997 to November 2002. Homocysteine levels, normalized aPC sensitivity ratio (aPCSR), and Factor V Leiden genotype were recorded for all 1011 patients. 394 patients had aPC-SR determined by mixing the patient plasma in 4 parts FV deficient plasma (FV-deficient-mix assay), and 617 patients had aPC-SR calculated without mixing (neat assay). Homocysteine did not significantly influence the aPC-SR when using the FV deficient assay. When aPC-SR was measured using the neat assay, homocysteine was found to correlate inversely with the degree of aPC resistance. The mean aPC-SR of FV Leiden-negative subjects measured using the neat assay was substantially lower than the expected normalized value of 1.0 that was obtained when aPC-SR was measured with the FV-deficient-mix assay. aPC resistance is common in patients being evaluated for possible hypercoagulability. In these patients, elevated plasma homocysteine levels is not associated with aPC resistance regardless of FV Leiden genotype suggesting that this is not the mechanism by which homocysteine exerts a prothrombotic effect.
Keywords: Homocysteine; APC resistance; thrombosis